Reliability of a gas analyzer to determine glycemia compared to the conventional laboratory method - Saldaña O, Ítalo Moisés (2014)
Objectives: To determine the glucose reliability results measured in a gas equipment as compared with a reference method commonly used in the laboratory. The Clinical and Laboratory Standards Institute (CLSI) guide EP9- A2 instructions were followed. Design: Descriptive study with non-probability sampling. Setting: Hospital Edgardo Rebagliati Martins, EsSalud, Lima, Peru. Materials: Blood sample of 234 subjects from the emergency services and intensive care unit. Methods: Blood glucose was processed with the ADVIA1800 equipment and the ABL800 gasometer. Results of both analyzers were compared following the mentioned guide directives, the Bland-Altman plot analysis and the Lin’s concordance correlation coefficient (CCC) calculation. Main outcome measures: Serum glucose concentration. Results: Average blood glucose levels obtained were 1.6 mg/dL higher for ABL800 than for ADVIA1800. Both methods showed a high positive correlation (beta coefficient 0.9995 and 95%, 95%CI 0.9994 to 0.9996). Glucose results for the method studied were acceptable, as confirmed with the Bland-Altman statistical analysis(0.9995 CCC value, 95%CI 0.9993 to 0.9996). Conclusions: The ABL800 analyzer is suitable for blood glucose monitoring, presenting an excellent correlation with the reference laboratory method.